Acute haemodynamic effects of felodipine during beta blockade in patients with coronary artery disease. - Culling, W (1984)
The acute effects of felodipine on left ventricular function and haemodynamics were studied in 11 patients with coronary artery disease. To block reflex sympathetic activation due to peripheral vasodilatation and to avoid effects secondary to changes in heart rate all patients received a standard regimen of beta adrenoceptor blockade and all measurements were made during sinus rhythm and right atrial pacing. At 30 minutes after an oral dose (0.075 mg/kg in solution) felodipine plasma concentration were 16.4 (3.5) nmol/l. A significant fall in systemic vascular resistance (30%) and increase in cardiac index (30%) occurred, whereas pulmonary vascular resistance was unchanged. Felodipine increased left ventricular ejection fraction and mean velocity of circumferential fibre shortening but had no effect on derivates of left ventricular pressure (dP/dt or dP/dt P-1) during sinus rhythm or pacing. Thus at the dosage used felodipine was a potent dilator of systemic arterioles but had no direct effect on left ventricular function.